Macroeconomic effects of social security privatization in a small unionized economy - Antonis Adam (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper analyses the effects of a pension system privatization in a unionized economy. Using an overlapping-generations framework we show that in an environment characterized by unemployment, a reform towards a private pension system in the steady state may result in lower levels of employment and capital stock. In this case even if the privatization increases the welfare of all future generations, the reduction in the welfare of the elderly due to reduced pension benefits may be greater and a Pareto improving transition to a private system may not be feasible. On the other hand if the reform leads to higher employment then a Paretoimproving pension privatization scheme can be constructed.
Keywords: J51; J32; H55; 330; public pensions; social security privatization; labour union; unemployment; Gesetzliche Rentenversicherung; Rentenreform; Privatisierung; Arbeitslosigkeit; Overlapping Generations; Kleines-offenes-Land; Gewerkschaftlicher Organisationsgrad; Wohlfahrtseffekt; Theorie